The age of anxiety : a history of America's turbulent affair with tranquilizers - Tone, Andrea, 1964- (Basic Books, 2009)
"Our reliance on anti-anxiety medication is a creation of the last half-century. When the first tranquilizer - Miltown - went on the market in 1955, pharmaceutical executives worried that there wouldn't be interest in stress relief in the form of a pill. At mid-century, talk therapy remained the treatment of choice. But Miltown quickly became a sensation - the first psychotropic blockbuster in American history. Patients seeking made-to-order tranquility emptied drugstores of the medication, forcing pharmacists to post signs reading "more Miltown tomorrow." By 1957, Americans had filled 36 million prescriptions. The drug's success revolutionized perceptions of anxiety and its treatment, inspiring the development of, other lifestyle drugs including Valium and Prozac." "In The Age of Anxiety, historian Andrea Tone draws on a broad array of original sources - manufacturers' files, FDA reports, letters, government investigations, and interviews with inventors, physicians, patients, and activists - to provide the first comprehensive account of the rise of America's tranquilizer culture. She transports readers from the bomb shelters of the Cold War to the scientific optimism of the Baby Boom generation, to the "just-sayno" pharmaceutical Puritanism of the late 1970s and 1980s to contemporary debates about anxiety and the newest drugs to treat it."--Jacket